Gene action conditioning resistance traits to spotted stem borer, Chilo partellus, in grain sorghum. - Muturi, P. W.; Mgonja, M.; Rubaihayo, P. (International Journal of Tropical Insect Science, 2019)
Understanding the mode of gene action conditioning traits of interest in sorghum is important for effective and efficient plant breeding programs. The objective of this study was to establish the nature of gene action for components that contribute to resistance to spotted stem borer, Chilo partellus, in grain sorghum. The experimental material consisted of seventeen sorghum lines with varying levels of resistance to C. partellus. Genetic analyses were performed using a line x tester method using Genstat statistical software. There was significant variation among the F1 for C. partellus resistance and grain yield. The general combining ability (GCA) for deadheart damage was significant (P ≤ 0.01) implying that this trait was governed by an additive type of gene action. Specific combining ability (SCA) for exit holes and stem tunneling were significant (P ≤ 0.01) suggesting that these characters were conditioned by both additive and non-additive types of gene action. Lines ICSA 472, ICSA 464, ICSB 474 contributed high levels of resistance to hybrids while IESV 93042 SH, IS 21879 and IESV 91131 DL were good sources of genes for high grain yield. This observation implied that grain yield and stem borer resistance traits should be considered in development of C. partellus resistant sorghum since a resistant line doesn’t necessarily yield high and vice versa. Generally, results of this study indicated that it would be possible to breed for high C. partellus resistance from this set of germplasm for cultivation by farmers in areas where the insect pest causes epidemics.